2015
DOI: 10.1038/srep10324
|View full text |Cite
|
Sign up to set email alerts
|

The cytosolic tail of the tumor marker protein Trop2 - a structural switch triggered by phosphorylation

Abstract: Trop2 is a transmembrane signaling glycoprotein upregulated in stem and carcinoma cells. Proliferation-enhancing signaling involves regulated intramembrane proteolytic release of a short cytoplasmic fragment, which is later engaged in a cytosolic signaling complex. We propose that Trop2 function is modulated by phosphorylation of a specific serine residue within this cytosolic region (Ser303), and by proximity effects exerted on the cytosolic tail by Trop2 dimerization. Structural characterization of both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 65 publications
(84 reference statements)
0
18
0
Order By: Relevance
“…In this motif, there is a serine at position 303, which may be phosphorylated by protein kinase C (PKC) ( Figure 1 ) [ 10 ]. This phosphorylation leads to conformational changes and affects the accessibility of functionally important regions of its cytoplasmic tail [ 11 ]. It has been shown that Trop2 extracellular domains can form dimers [ 12 ].…”
Section: Gene and Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…In this motif, there is a serine at position 303, which may be phosphorylated by protein kinase C (PKC) ( Figure 1 ) [ 10 ]. This phosphorylation leads to conformational changes and affects the accessibility of functionally important regions of its cytoplasmic tail [ 11 ]. It has been shown that Trop2 extracellular domains can form dimers [ 12 ].…”
Section: Gene and Proteinmentioning
confidence: 99%
“…It has been shown that Trop2 extracellular domains can form dimers [ 12 ]. Using molecular dynamic simulations, Pavšič et al later demonstrated that the Trop2 dimerization interface extends to the transmembrane part [ 11 ]. However, the effect of dimerization on Trop2 function has not yet been studied in detail.…”
Section: Gene and Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report demonstrated that the EpCAM homologous protein Trop-2, with similar functionality, is phosphorylated in Trop-IC, enabling conformational switching. 15 , 16 In light of this, the study aimed to employ an in silico analysis for prediction of novel EpCAM PTM sites. Further, we checked the biological/functional relevance of the PTM based on the impact of the putative PTM on conformational dynamics and functionality of the human EpICD.…”
Section: Introductionmentioning
confidence: 99%
“…According to molecular dynamics simulations the dimer is additionally stabilized by dimerization of the transmembrane helices of the two subunits [ 11 ]. However, the dimerization interface most probably does not extend to the cytosolic tail (EpIC) considering the analogy to EpCAM paralogue Trop2—while it has been demonstrated that cytosolic tail of Trop2 has a strong potential to form α-helical structure, dimers were not detected [ 33 ]. For EpIC no stable or induced secondary structure has been observed (our unpublished results).…”
Section: The Biological Unit Of Epcam Is a Cis-dimermentioning
confidence: 99%